Analysis of results of natural fire tests at Zaporizhzhia NPP - Troshkin, S. E. (My University, 2023)
The study of the temperature regime of fires is a relevant issue since vertical cable tunnels differ in geometric configuration, types of cables laid in them, fire loads, and aerodynamic characteristics. This can lead to differences in the temperature regime of fires in such tunnels compared to both the standard regime and among themselves. In this case, it is impossible to guarantee compliance of the fire resistance limits of tested structures. In such a situation, the safety of people and property during fires in vertical cable tunnels of nuclear power plants may be significantly compromised.
Keywords: temperature regime; температурний режим; vertical cable tunnel; вертикальний кабельний тунель